FACILITY LAYOUT PLANNING IN SMALL INDUSTRY TO INCREASE EFFICIENCY (CASE STUDY: BIG BOY BAKERY, BATAM, KEPULAUAN RIAU, INDONESIA) - Fuad Dwi Hanggara (Center for Study and Journal Management FTI UMI, 2020)
In the food industry competition in Indonesia, Big Boy Bakery which is a small-scale food industry competes with the food industry both small and large scale. This pressured Big Boy Bakery to continue to grow both in increasing the quality and quantity of production. One method that will be used is planning the layout of facilities at the production site so that it becomes the basis for consideration of the placement of important elements in the design of the construction of future production sites. Facility layout is carried out because there are differences in the distance between production operations and other production operations which cause inefficiencies in productivity. In this problem approach the method used in Big Boy Bakery layout planning is the Systematic Layout Planning (SLP) method. The function of SLP is to improve the layout of Big Boy Bakery, by finding alternatives that have been considered with important elements in production operations that have been taken into account at either the level of interaction, or other needs. Placement of important elements such as proper production operations, will reduce travel costs, and waste time, so that the planned layout can provide increased productivity efficiency. With the proposed spatial planning made, it is hoped that it can make a significant contribution to the development of Big Boy Bakery.